Development and characterization of an animal model of Japanese encephalitis virus infection in adolescent C57BL/6 mouse - Aarti Tripathi; Arup Banerjee; Sudhanshu Vrati (The Company of Biologists, 2021)
A mouse-adapted isolate of Japanese encephalitis virus (JEV), designated as JEV-S3, was generated by serially passaging the P20778 strain of the virus in 3- to 4-week-old C57BL/6 mice. Blood-brain barrier leakage was evident in JEV-S3-infected mice, in which viral antigens and RNA were consistently demonstrated in the brain, along with infiltration of activated immune cells, as evidenced by an increased CD45+CD11b+ cell population. Histopathology studies showed the presence of perivascular cuffing, haemorrhage and necrotic foci in the virus-infected brain, conforming to the pathological changes seen in the brain of JEV-infected patients. Mass spectrometry studies characterized the molecular events leading to brain inflammation in the infected mice. Notably, a significant induction of inflammatory cytokines, such as IFNγ, IL6, TNFα and TGFβ, was observed. Further, genome sequencing of the JEV-S3 isolate identified the mutations selected during the mouse passage of the virus. Overall, we present an in-depth characterization of a robust and reproducible mouse model of JEV infection. The JEV-S3 isolate will be a useful tool to screen antivirals and study virus pathogenesis in the adolescent mouse model.